Obesity as risk factor associated with hypertension among nursing professionals of a national philanthropy health institution - Oliveira, Aline Furtado Carlos de; Nogueira, Maria Suely (Revista da Escola de Enfermagem da USP, 2010)
The present study analyzed the relationship between obesity and high blood pressure among nursing professionals of a philanthropic institution, with a view to the early detection of possible cases of hypertension. The study population consisted of 147 nursing professionals of ages between 20-70 years. The researcher performed structured, individual, interviews at the work site of those professionals, 91.8% of which were women; 29.2% were older than 40 years; 11.6% had a SBP>;140mmHg and 6.8% DBP>;90mmHg; 12.2% had obesity class I-II; 38.1% of women with a WHP>;0.85, 12.2% in the age range of 40-49 years; 2.1% of men with a WHR>;1.0, 1.4% in the age range of 40-49 years. It was found that, though nursing professionals know the severity of the disease and the importance of changing their life habits, they still find it difficult to adopt that behavior, which suggests the need to implement educational programs at the work site to help them to change their behaviors.